2011
DOI: 10.1371/journal.pone.0027834
|View full text |Cite
|
Sign up to set email alerts
|

Recent Speciation in Three Closely Related Sympatric Specialists: Inferences Using Multi-Locus Sequence, Post-Mating Isolation and Endosymbiont Data

Abstract: Shifting between unrelated host plants is relatively rare for phytophagous insects, and distinct host specificity may play crucial roles in reproductive isolation. However, the isolation status and the relationship between parental divergence and post-mating isolation among closely related sympatric specialists are still poorly understood. Here, multi-locus sequence were used to estimate the relationship among three host plant–specific closely related flea beetles, Altica cirsicola, A. fragariae and A. viridic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 75 publications
1
29
1
Order By: Relevance
“…Considering the incomplete post-mating reproductive isolation181920, we suggest near perfect assortative mating has evolved. Differing from many studies in which allochronic factors play an important role in reproductive isolation and speciation41, allochronic isolation contribute little in the present system.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Considering the incomplete post-mating reproductive isolation181920, we suggest near perfect assortative mating has evolved. Differing from many studies in which allochronic factors play an important role in reproductive isolation and speciation41, allochronic isolation contribute little in the present system.…”
Section: Discussionmentioning
confidence: 92%
“…The insects were fed their respective host plants ( D. indica fed to AF and G. nepalens fed to AV) in growth chambers at 16:8 LD and 25°C181920. To eliminate the possible effects due to different physiology, virgin captive-bred offspring were used for no-choice tests.…”
Section: Methodsmentioning
confidence: 99%
“…Most phytophagous beetles feed on a limited range of taxonomically related plant species, and some are highly specialized on one or a few host plant species (Winkler & Mitter 2008;Chapman 2009;Xue et al 2011). Studies on host specialization and adaptation have revealed that plant chemistry plays an important role in the evolution of plant-beetle associations (Feeny 1975;St€ adler 1992;Landolt & Phillips 1997;Rasmann & Agrawal 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The high rate of diversi cation among host-speci c herbivorous insects is thought to result from their shift and specialization to distinct host-plant species, creating conditions that promote reproductive isolation and contribute to the process of speciation [1][2][3]. A model herbivore that has been used to address questions about host plant specialization, reproductive isolation, and ecological speciation is the leaf beetle genus Altica (Coleoptera: Chrysomelidae) [4][5][6][7][8][9][10]. This group has undergone rapid divergence that is largely associated with host plant use.…”
Section: Introductionmentioning
confidence: 99%